Mountbatten : Eighty Years in Pictures - Mountbatten; Louis and Earl Mountbatten (London Macmillan, 1979)
Lord Mountbatten has made a personal selection which provides a pictorial record of an extraordinary career. Earl Mountbatten of Burma has played a leading role in many of the great events of this century.
Includes Bibliographical Note, Index and Colored Illustrations.
Keywords: Great Britain